Existence of three solutions for perturbed nonlinear difference equations - Shapour Heidarkhani; Mohsen Khaleghi Moghadam (Opuscula Mathematica, 2014)
Using critical point theory, we study the existence of at least three solutions for perturbed nonlinear difference equations with discrete boundary-value condition depending on two positive parameters.